1998
DOI: 10.1542/peds.101.1.e9
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Later Cognitive and Academic Outcomes

Abstract: ABSTRACT.Objective. This study examines the associations between duration of breastfeeding and childhood cognitive ability and academic achievement over the period from 8 to 18 years using data collected during the course of an 18-year longitudinal study of a birth cohort of >1000 New Zealand children.Method. During the period from birth to age 1 year, information was collected on maternal breastfeeding practices. Over the period from 8 to 18 years, sample members were assessed on a range of measures of cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
205
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(234 citation statements)
references
References 22 publications
15
205
2
4
Order By: Relevance
“…39,40 Thus, It can be considered that the EBF may effect in later life, as noted in a meta-analysis reported that breastfeeding decreased by 26% (CI95%: 22-30) the chance of overweight/obesity and checked protective action for diabetes type 2, 39 and in the studies of adult intelligence and school performance show evidence of positive effects of EBF on these abilities. 41,42 The same was observed in a cohort study conducted in Brazil, which show that the more enduring the period of breastfeeding in infancy, the higher the levels of intelligence and an average income in adulthood to 30 years. 42 The positive aspects of EBF involving the parent woman establish interface with acceleration of postpartum weight loss, reduce incidence of anemia and reduces the chance of developing breast, ovary and endometrial cancer, as well as osteoporosis.…”
Section: Early Interruption Of Exclusive Breastfeeding In Brazilsupporting
confidence: 66%
“…39,40 Thus, It can be considered that the EBF may effect in later life, as noted in a meta-analysis reported that breastfeeding decreased by 26% (CI95%: 22-30) the chance of overweight/obesity and checked protective action for diabetes type 2, 39 and in the studies of adult intelligence and school performance show evidence of positive effects of EBF on these abilities. 41,42 The same was observed in a cohort study conducted in Brazil, which show that the more enduring the period of breastfeeding in infancy, the higher the levels of intelligence and an average income in adulthood to 30 years. 42 The positive aspects of EBF involving the parent woman establish interface with acceleration of postpartum weight loss, reduce incidence of anemia and reduces the chance of developing breast, ovary and endometrial cancer, as well as osteoporosis.…”
Section: Early Interruption Of Exclusive Breastfeeding In Brazilsupporting
confidence: 66%
“…A sucção desempenha importante papel, possibilitando desenvolvimento adequado das funções de respiração, mastigação, deglutição e fala, reduzindo a probabilidade de ocorrência de alterações fonoaudiológicas [3][4][5] . Outro benefício demonstrado na literatura referese à habilidade cognitiva e o desempenho escolar, uma vez que a duração crescente da amamentação natural foi associada ao aumento estatisticamente significante no quociente de inteligência, compreensão da leitura, da matemática e outras habilidades escolares 6 . Em alguns casos o aleitamento materno exclusivo pode estar prejudicado como em recém nascido pré-termo (RNPT), em que ocorre, especificamente, uma imaturidade global, incluindo o sistema estomatognático, que dificulta a realização da função de sucção e, consequentemente, a alimentação por via oral [7][8][9][10][11] .…”
Section: Descritoresunclassified
“…After control of confounding variables, there was a significant advantage to breast-fed children on a picture vocabulary test at 8 y of age and on nonverbal ability, mathematics, and sentence completion at 15 y. A few studies have examined reading ability or school attainment, and breast-fed children tended to do better (Ounsted et al, 1984;Rogan & Gladen, 1993;Horwood & Fergusson, 1998). The most recent follow-up study in a New Zealand cohort of 1000 children reported that breastfeeding is associated with small but detectable increases in cognitive ability and academic achievement, extending from 8 to 18 y (Horwood & Fergusson, 1998).…”
Section: Breastfeeding and Cognitionmentioning
confidence: 99%
“…A few studies have examined reading ability or school attainment, and breast-fed children tended to do better (Ounsted et al, 1984;Rogan & Gladen, 1993;Horwood & Fergusson, 1998). The most recent follow-up study in a New Zealand cohort of 1000 children reported that breastfeeding is associated with small but detectable increases in cognitive ability and academic achievement, extending from 8 to 18 y (Horwood & Fergusson, 1998). The difference was significant after adjustment for social and family history, including maternal age, education, social economic status, marital status, smoking during pregnancy, family living conditions, and family income, and perinatal factors, including gender, birth weight, child's estimated gestational age, and birth order in the family.…”
Section: Breastfeeding and Cognitionmentioning
confidence: 99%